Multimodality imaging of a rare pulmonary artery sessile mass: a case report. Issue 2 (4th January 2021) - Piscitelli, Laura; Dentamaro, Ilaria; Pezzicoli, Gaetano; D'Agostino, Carlo
Abstract: Background : Primary pulmonary artery masses are unusual entities that mimic pulmonary embolism (PE) in clinical presentation and on imaging studies. It is necessary to perform advanced diagnostic exams, such as transesophageal echocardiography (TEE) and cardiac magnetic resonance imaging (MRI), to determine the proper diagnosis. In unclear cases, laboratory findings, morphological follow-up, and response to anticoagulant therapy can help to clarify the diagnosis. Case summary : A 47-year-old previously healthy man with worsening effort dyspnoea underwent chest computed tomography (CT) for suspicion of PE, which showed a pedunculated eccentric mass at the origin of the pulmonary artery causing severe stenosis. The patient was started on anticoagulation therapy, but, after TEE and cardiac MRI, a neoplastic fibroelastic mass was suspected. Unexpectedly, 18 fluorodeoxyglucose (FDG) positron emission tomography (PET)-CT revealed a unique area of glucose uptake in the superior lobe of the left lung and not in the pulmonary artery. The biopsy was consistent with pleomorphic high-grade lung sarcoma. After 3 months of chemotherapy, a CT scan showed progression of the lung disease with no change in the arterial mass, which was therefore confirmed as pulmonary fibroelastoma. Discussion : Due to the rarity of pulmonary artery tumours, they can be initially misdiagnosed as PE or a metastasis of a lung sarcoma. Three-dimensional TEE and cardiac MRI are particularly useful in differentiating tumours from PE.